KETIMPANGAN SEBAGAI PENYEBAB KONFLIK: KAJIAN ATAS TEORI SOSIAL KONTEMPORER - Muhamad Zuldin (TEMALI : Jurnal Pembangunan Sosial, 2019)
This article reviews the relationship between inequality and social conflict in society. This literature review finds that there are at least four schools of thought in contemporary conflict theory that examine the relationship of inequality to conflict. The first is the flow of positive thought which includes the theory of structural conflict. Second is the flow of humanism thinking which consists of symbolic interactions and social construction theory. The third is the school of thought which consists of the thoughts of Jurgen Habermas and Pierre Bourdieu. And the last is a multi-disciplinary school built by Johan Galtung and Anthony Giddens. The four schools of thought develop classical conflict theory, especially Marx's thought that argues that economics is the only factor of conflict in society.